Influence of Р6m5 Steel Structure on Modes of Low Temperature Nitrocementation - Begatov Jahongir Mukhammadjonovich; Platoshina Malika Mirkamal kizi (Research Parks Publishing LLC, 2023)
The article discusses a method of hardening tools made of high-speed steel grade P6M6 in order to obtain higher wear resistance. Research has been carried out on the effect of final tempering temperature on the hardness of steel, and research has also been carried out to determine the optimal temperature of nitrocarburization, in order to obtain high hardness values with a general reduction in tool processing time. To determine the effect of tempering temperature on the hardness of Р6M5 steel, samples were prepared that were quenched from standard temperatures of 1200-1230°C and subjected to tempering from different temperatures. Studies have shown that the highest hardness values are achieved when tempering 540-560°С, and with a further increase in tempering temperature, up to a temperature of 620°С, there is no critical decrease in steel hardness. This circumstance makes it possible to carry out a single final tempering at a temperature of 600-620°С.